2019
DOI: 10.1016/j.anbehav.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Developmental stage-dependent response and preference for host plant quality in an insect herbivore

Abstract: Larval-derived nutritional reserves are essential in shaping insects' adult fitness. Early larval instars of many Lepidopteran species are often sessile, and the conditions experienced by these larvae are often highly dependent on the mother's oviposition choice. Later larval stages are more mobile and therefore can choose their food whenever alternatives are available. We tested how feeding on a drought-exposed host plant impacts life history in an insect herbivore, and whether the observed responses depended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 62 publications
4
34
0
Order By: Relevance
“…To conclude, we found mostly beneficial effects of moderate plant drought-stress on insect performance, indicating that the previously suggested negative impact of reduced precipitation is likely due to extreme desiccation [22,34]. Indeed, this pattern is confirmed by work finding reduced survival and body mass of larvae fed on severely water-stressed plants [34].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To conclude, we found mostly beneficial effects of moderate plant drought-stress on insect performance, indicating that the previously suggested negative impact of reduced precipitation is likely due to extreme desiccation [22,34]. Indeed, this pattern is confirmed by work finding reduced survival and body mass of larvae fed on severely water-stressed plants [34].…”
Section: Discussionsupporting
confidence: 81%
“…In general, our findings suggest a higher larval performance on moderately water-stressed plants. Intriguingly, larvae of the same age but faced with severe plant water stress have a low performance in terms of both reduced survival and body mass [34].…”
Section: Discussionmentioning
confidence: 99%
“…The effects on occupancy are limited to large-scale annual differences with limited spatial variation, while for abundance the effects are more variable and also more local due to, for example, behavioural interactions with the local topography and microclimate (Eilers et al 2013, Lawson et al 2014. Any effects on abundance will also have indirect impacts on occupancy: for example, if summer drought reduces the quantity and quality of host plant available for larvae, the consequent reduction in abundance would also increase extinction risk in the next year (Salgado and Saastamoinen 2019).…”
Section: Discussionmentioning
confidence: 99%
“…nest presence showed significant negative relationships with PC1 and PC2) in addition to sites with higher host plant coverage and drought stress, neither PC1 nor PC2 were found to be related to overwintering survival. Finally, we have some experimental evidence that suggests that feeding on drought exposed host plants does, at least in some families, directly increase larval performance (pre-diapause larvae: Rosa et al 2019 & post-diapause larvae: Salgado & Saastamoinen, 2019) that seems to even translate to increased adult performance (Salgado & Saastamoinen, 2019). Even though the impact of drought on host plant quality was not assessed here, previous studies on other systems have shown that plants under drought stress often accumulate nutrients, such as carbon and nitrogen, that can enhance the performance of insect herbivores (Gutbrodt, Mody, & Dorn, 2011;Mattson & Haack, 1987).…”
Section: Testing For Oviposition Site Preference and Effects On Larvamentioning
confidence: 95%
“…Hanski et al, 2017;Schulz, Vanhatalo, & Saastamoinen, 2019) and combine it with detailed field assessments to ask whether oviposition preferences vary across years and whether mothers generally choose locations that enhance their offspring's overwinter survival. As Finland is the northern range limit of these butterfly species, with relatively short time window for larval development, and based on our recent findings that larval performance may be increased by feeding on droughtexposed host plants (Rosa, Minard, Lindholm, & Saastamoinen, 2019;Salgado & Saastamoinen, 2019), we hypothesize that drier microhabitats are generally favoured by the females but may be disadvantageous for the larvae during particularly warm and dry years.…”
Section: Introductionmentioning
confidence: 93%